2013
DOI: 10.3329/jdmc.v21i2.15368
|View full text |Cite
|
Sign up to set email alerts
|

A Young Child with Sickle Cell Beta Thalassemia: A Case Report and Review of Literatures

Abstract: J Dhaka Medical College, Vol. 21, No. 2, October, 2012, Page 245-249 DOI: http://dx.doi.org/10.3329/jdmc.v21i2.15368

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…2). Among the 8 studies selected outside India in South Asia, there were 7 case reports with 2 case studies each from Pakistan, Sri Lanka, Bangladesh and one from Nepal [22][23][24][25][26][27][28]. No eligible study was identified from Maldives and Bhutan.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2). Among the 8 studies selected outside India in South Asia, there were 7 case reports with 2 case studies each from Pakistan, Sri Lanka, Bangladesh and one from Nepal [22][23][24][25][26][27][28]. No eligible study was identified from Maldives and Bhutan.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the usage of HU for infants and children age 9 months or older who are asymptomatic or having infrequent pain episode has not adequately analysed among Indian patients. Therapeutic usage of HU for SCD have also been noted in couple of case reports from Pakistan, Bangladesh, Nepal and one descriptive cross-sectional study from Sri Lanka [21,22,26,28]. However, particulars of different dosing regimens in practice, toxicities and detailed response to HU therapy is largely unknown.…”
Section: Discussionmentioning
confidence: 99%